Small RNA perspective of physical exercise-related improvement of male reproductive dysfunction due to obesity - Lin, Tingting; Zhang, Shuyu; Zhou, Yuchuan; Wu, Ligang; Liu, Xinmei; Huang, Hefeng (Frontiers in Endocrinology, 2022)
Purpose To study whether physical exercise can effectively ameliorate obesity-induced abnormalities in male fertility and provide a new perspective on the role of small noncoding RNAs in spermatogenesis in obese male mice. Methods In this study, four-week-old C57/Bl6 male mice were randomly allocated to receive a control diet, a high-fat diet or physical exercise intervention for 40 weeks. Purified round spermatids and spermatozoa were obtained after intervention. Sperm motility, concentration, the ability of the sperm to undergo capacitation and acrosome reaction were assessed. Small RNA sequencing was conducted on round spermatids and spermatozoa. The small noncoding RNAs expression pattern was systematically analyzed. Results The spermatozoa concentration and percentage of motile spermatozoa, the capacitation and acrosome reaction, and the reproductive success rate, including mating success and pregnancy success, were decreased or delayed in the obesity group compared with controls. Physical exercise was able to restore the parameters to normal levels. Three microRNAs were consistently upregulated and 5 were downregulated in round spermatids and epididymal spermatozoa between the obesity and control groups. Conclusions This report provides evidence that the adverse effects of obesity could be offset after physical exercise. small noncoding RNAs, especially microRNAs in germ cells, may play an important role in the effects of obesity and physical exercise on spermatozoa.